Intermediation Services and Search Frictions - Christian Holzner; Makoto Watanabe (Tinbergen Institute, 2017)
In many countries Public Employment Agencies (PEA) offer intermediation services to help as many people as possible to find work by bringing together supply and demand. Using a unique vacancy-level data-set on the number of applicants, we find positive effects of the intermediation services on mitigating search frictions. In particular, we show that applications coming via the PEA are more evenly distributed across vacancies than the applications coming via other search channels. This holds for the total number of applicants as well as the suitable number of applicants. Our results suggest that the market operated by the PEA attains more coordinated job applications compared to other search channels.
Keywords: J6; 330; Intermediation; Public Employment Agency